2014
DOI: 10.1016/j.bbmt.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Relapse in Adults with Acute Lymphoblastic Leukemia after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Central nervous system (CNS) relapse after allogeneic hematopoietic stem cell transplantation (HSCT) confers a poor prognosis in adult patients with acute lymphoblastic leukemia (ALL). Preventing CNS relapse after HSCT remains a therapeutic challenge, and criteria for post-HSCT CNS prophylaxis have not been addressed. In a three-center retrospective analysis, we reviewed the data for 457 adult patients with ALL who received a first allogeneic HSCT in first or second complete remission (CR). All patients receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 19 publications
(20 reference statements)
1
23
0
Order By: Relevance
“…The use of tyrosine kinase inhibitors (TKIs) is the most effective method for suppressing BCR-ABL1 tyrosine kinase activity (4,5). However, single-agent TKI has not produced sustained responses in BCR-ABL1 + B-ALL, as this specific subtype of B-ALL is likely to develop significant involvement of the CNS, which acts as a ‘sanctuary’ site for leukemic cells to escape anticancer treatments (68). Therefore, understanding the molecular mechanisms of BCR-ABL1 + B-ALL associated with CNS metastasis is a critical step to improve therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…The use of tyrosine kinase inhibitors (TKIs) is the most effective method for suppressing BCR-ABL1 tyrosine kinase activity (4,5). However, single-agent TKI has not produced sustained responses in BCR-ABL1 + B-ALL, as this specific subtype of B-ALL is likely to develop significant involvement of the CNS, which acts as a ‘sanctuary’ site for leukemic cells to escape anticancer treatments (68). Therefore, understanding the molecular mechanisms of BCR-ABL1 + B-ALL associated with CNS metastasis is a critical step to improve therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with a past study completed by Hamdi et al in adult ALL patients, suggesting that prior CNS disease indicates higher relapse rates and overall poorer prognosis after transplant. 16 Notably, patients in our CB cohort with CNS failure all had prior involvement, suggesting that 6 Gy may not be adequate in this population and that these patients may require treatment intensification. Extrapolating from the pediatric ALL literature, higher dose CB may be required in this setting.…”
Section: Discussionmentioning
confidence: 88%
“…Hamdi reported that the CNS relapses occurred at a median of 231 days in CNS leukemia patients after receiving allo-HSCT [ 6 ]. It is noteworthy, among 6 patients with no post-HSCT CNS therapy, the median time was 72.5 days.…”
Section: Discussionmentioning
confidence: 99%
“…The central nervous system (CNS) acute lymphocytic leukemia (ALL) accounts for more than 30% of all ALL relapses and confers a poor prognosis [ 1 , 2 ]. Since cranial or craniospinal radiotherapy (CRT) for CNS ALL has been almost abandoned due to its long-term side effects [ [3] , [4] , [5] ], performing allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a good choice for treating CNS ALL due to the lower relapse rate [ 6 ]. Even in this setting, the incidence of CNS relapse is as high as 13% in patients with a history of CNS involvement before transplantation compared with the overall incidence of 4% in the entire cohort [ 6 ].…”
Section: Introductionmentioning
confidence: 99%